Evaluation of Polysynchronous Learning of Statistical Materials in High School - Syaifuddin, Mohammad; Zaqiya, Fadhila Nur; Jamil , Anis Farida (Journal of Education Reseach and Evaluation, 2023)
Evaluation of learning implementation is critical. The emphasis is mostly on polysynchronous learning. The purpose of this study is to assess polysynchronous learning of statistical material in high school. The type and approache  of this study is descriptive-quantitative. The subjects of the study were 29 high school students. Observation, tests, and questionnaires were used to collect data on the implementation of polysynchronous learning, problem-solving ability, and student learning independence. Data analysis is performed in three stages: scoring, computing percentages, and generating conclusions based on the provided categories. The results demonstrated that polysynchronous learning can be implemented properly utilizing Whatsapp for asynchronous and Google Meet for synchronous. Pupils with very high, high, medium, and low problem-solving talents are represented by 11, 7, 5, and 6 students, respectively. The number of pupils with learning independence ranges from very high to high to medium, with as many as 6, 19, and 4 students in each category. Students have the ability to solve mathematical problems and the independence to learn high-level categories, which makes it possible for the implementation of polysynchronous learning of statistical material to be carried out in an appropriate manner. The findings of this study suggest that educators can make use of polysynchronous learning to enhance the problem-solving abilities and independent learning capabilities of their pupils, regardless of whether they are living in a pandemic or new-normal environment.